2014
DOI: 10.3389/fpsyt.2014.00098
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Neurobiology of Bipolar Disorder

Abstract: From a neurobiological perspective there is no such thing as bipolar disorder. Rather, it is almost certainly the case that many somewhat similar, but subtly different, pathological conditions produce a disease state that we currently diagnose as bipolarity. This heterogeneity – reflected in the lack of synergy between our current diagnostic schema and our rapidly advancing scientific understanding of the condition – limits attempts to articulate an integrated perspective on bipolar disorder. However, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 269 publications
(412 reference statements)
3
127
0
8
Order By: Relevance
“…However, other work has shown a significant correlation between gene expression in blood and brain that includes many genes related to schizophrenia [15]. There is accumulating evidence that altered immunological functioning and immune system activation may be associated with states of depression [25] as well as mania [26]; these functions also appear to be generally disrupted in the pathophysiology of BD [27,28]. Lithium has been shown to decrease cyclooxygenase-2 and prostaglandin activity, and this mechanism has been proposed as a contributor to its therapeutic action in BD [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, other work has shown a significant correlation between gene expression in blood and brain that includes many genes related to schizophrenia [15]. There is accumulating evidence that altered immunological functioning and immune system activation may be associated with states of depression [25] as well as mania [26]; these functions also appear to be generally disrupted in the pathophysiology of BD [27,28]. Lithium has been shown to decrease cyclooxygenase-2 and prostaglandin activity, and this mechanism has been proposed as a contributor to its therapeutic action in BD [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations in bipolar patients show that repeated episodes or residual symptoms enhance the risk of future recurrences (De Dios et al, 2012), while aggravating deterioration and volumetric changes of brain tissue (Strakowski et al, 2002;Moorhead et al, 2007;Lim et al, 2013). Recent studies have even shown that neuropsychological deficits may persist during euthymic state, corroborating the idea of a continuous aggressive inflammatory environment (for a review on neurobiology of BD, see Maletic and Raison, 2014). The enhanced risk of developing comorbidities, as long as the disorder progresses, would be supported by microgliainduced cell death, as proposed in our hypothesis.…”
Section: Possible Experimental Designmentioning
confidence: 87%
“…However, there were also two regions that had a stronger relationship between these imaging modalities in the bipolar versus healthy control group (i.e., coupling was enhanced), the left temporal pole and left inferior temporal gyrus. Many of these regions have been previously implicated by functional imaging studies as having a role in bipolar disorder (Cerullo, Adler, Delbello, & Strakowski, 2009; Gruber, Rogowska, & Yurgelun‐Todd, 2004; Keener & Phillips, 2007; Maletic & Raison, 2014; Strakowski et al., 2011; Townsend et al., 2012; Whitton, Treadway, & Pizzagalli, 2015; Yoshimura et al., 2014), which suggests that the altered relationship between fT1ρ and BOLD is related to the illness. For instance, numerous studies have shown that functional activity in the striatum is altered in bipolar disorder during the completion of reward tasks (Caseras, Lawrence, Murphy, Wise, & Phillips, 2013; Whitton et al., 2015; Yip, Worhunsky, Rogers, & Goodwin, 2014) and reduced during fear perception tasks (Killgore, Gruber, & Yurgelun‐Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%